THE ROLE OF ONLINE COMMUNITY ON CONSUMERS’ PURCHASE DECISION-MAKING: A NETNOGRAPHY STUDY - Nurhidayah Rosely; Suhaily Mohd Ramly; Ayu Kamareenna Abdullah Thani (International Journal of Accounting, Finance and Business, 2024)
The prominence of online social media communities greatly influences consumer purchase decision-making, particularly in the hospitality and tourism industry. Online communities facilitate an avenue for knowledge accumulation and educating others, serve as a point of reference in assisting consumers’ purchase decision-making, and pose a great challenge for service providers in crafting their marketing strategies. This study elucidates the role of the online community towards knowledge and information sharing, in which community members can learn, engage, and identify suitable accommodation from others' experiences. Based on netnography study, this research endeavored to explore an exhaustive and contextualized account through the interpretation of the meanings of the text in the form of consumers’ comments on the sharing posts by the online community members. The data were analysed using thematic analysis, and five themes materialised from this study; social learning, hedonic value, subjective value, experiential value, and dissonance feeling. It is substantiated that online communities not only facilitate information and knowledge sharing but also become a platform for the members to express and share similar emotions and feelings from their consumption experiences, enabling the community members to satisfy affiliation and relatedness needs. This present study is inspired by the development of online communities, particularly in social media networks, that facilitate consumer purchase decision-making and behaviour from the lens of online community members' purchase experiences, specifically on hotel reviews, which should be taken seriously by the service providers. Further, this research contributes to scholastic and organizational proficiency in the Malaysian context by comprehending the exact grounds of the role of the online community in social media networks towards consumers’ purchase decision-making.